Case Report of Successful Childbearing after Conservative Surgery for Cervical Mullerian Adenosarcoma - Seiji Kanayama; Masako Nakamura; Hidekazu Oi; Sumire Sugimoto; Yoshikazu Sasaki; Tomoko Uchiyama; Chiho Ohbayashi; Hiroshi Kobayashi (Hindawi Limited, 2017)
Mullerian adenosarcoma (MA) is a rare tumor variant with low malignancy potential and is reported to account for 8% of all uterine sarcomas. Cervical MAs are reported to occur in relatively younger patients with the mean age of 27 years, while those in the uterine corpus generally present in postmenopausal women. Due to the rarity of cervical MAs, optimal management for these patients (especially younger women) is still under exploration. Here, we describe a case of cervical MA in a woman of reproductive age who was treated by fertility-preserving surgery and successfully delivered a child 18 months later.